Taking A Second Look At Traditional Institutional Arrangements For Transboundary Water Governance In Africa - Sullivan, Amy (2009)
In sub-saharan Africa, there are around 63 transboundary river basins whose water cut across nations, catchments and regions. Most formal management of transboundary water is done through treaties, agreement and protocols between the states which share a given water source. However traditional arrangement and customary law still govern a large portion of water use especially in rural areas. Efficient development and management of resource in these basins require cooperation among the riparian countries and institutional arrangements that expects the complexity of sharing water recource between different users and uses.